Varchi, Bronzo, Benvenuto… Ut pictura poësis sub specie mortis - Dubard de Gaillarbois, Frédérique (Actual Problems of Theory and History of Art, 2021)
In this paper, we will show how death provided plenty of personal, collective, spontaneous, professional occasions for humanists and artists to work together and to compare their skills. If funeral occasions were initially used by Varchi to prove poësia superiority to pictura according to a predictable and convenient pattern as demonstrated at the funerals of Stefano Colonna, Lucrezia dei Medici, which involved collaborative efforts by Benedetto Varchi and Agnolo Bronzino, he then moved forward. His growing and late predilection for two genres — the “sub imagine” poem and the epitaph, shown at the funerals of Eleonora, Giovanni, and Garcia dei Medici, and through that of Giovanni Cellini,  — offered a fortunate, though neglected, synthesis between figurative arts and poetry, allowing him to elaborate a pictorial and sculptural poetry. Michelangelo’s funerals, in which Varchi played a major role as an orator and iconographist, enacted the dépassement of the paragonian approach in a baroque funerals, that demonstrate the converging and complementarity of all arts, writings, and languages.
Keywords: death; funerals; paragone; Benedetto Varchi; Bronzino; Benvenuto Cellini; epitaph; de imagine